Effect of Selenium Application and Growth Stage at Harvest on Hydrophilic and Lipophilic Antioxidants in Lamb’s Lettuce (Valerianella locusta L. Laterr.) - Liubov Skrypnik; Tatiana Styran; Tamara Savina; Nadezhda Golubkina (Plants, 2021)
Lamb’s lettuce (Valerianella locusta L. Laterr.) is a leafy green vegetable that is rich in various biological active compounds and is widely used in ready-to-eat salads. The cultivation conditions and growth stage could affect the secondary metabolism in plants and thereby modify their food value. In the present study, the effect of selenium (Se) application in various concentrations (5.0, 10.0, and 20.0 µM) on the contents of Se, phenolic compounds, vitamin C, carotenoids, chlorophylls, and antioxidant activity of hydrophilic and lipophilic extracts of lamb’s lettuce harvested at three growth stages (38, 52, and 66 days after sowing (DAS)) was studied. Se application significantly increased the Se concentration in the shoots (up to 124.4 μg g−1 dry weight), as well as the contents of chlorogenic acid, total flavonoids, total phenolics, ascorbic acid, chlorophyll b, and the antioxidant activity of hydrophilic and lipophilic extracts. A higher content of phenolic compounds and higher antioxidant activity of hydrophilic extracts was observed at the first growth stage (38 DAS). On the contrary, higher contents of lipophilic compounds (chlorophyll a, chlorophyll b, lutein, β-carotene) and higher antioxidant activity of lipophilic extracts were found for shoots harvested at later stages (52 and 66 DAS).